Inter-rater and Intra-rater Reliability of Het’s MMT in Pelvic Floor Assessment - Dhara Santosh Agnihotri; Anjali Ravindra Bhise; Arati Vinay Mahishale; Vandana K. Saini; Shila Bhagwanji Amersheda; Yojana Navneet Mange; Samiksha Gupta; Ushma Bhojani; Garima Biswas (Journal of the Scientific Society)
Objective: Pelvic floor dysfunctions (pfds) such as urinary incontinence, pelvic organ prolapse, and vaginismus are very common and are affecting the quality of life of the female suffering through it. The pelvic floor muscles can be in spasm, thus resulting in the inability to relax or the pelvic floor muscles can be extremely weak or loose, resulting in the inability to contract strongly and completely. The spasmodic pelvic floor can result in vaginismus, dyspareunia, chronic pelvic pain, constipation, etc., Moreover, a weak pelvic floor can lead to issues such as urinary incontinence, pelvic organ prolapse, and sexual dysfunction. There is a scarcity of a valid and reliable scale that assesses both the components of pfd. Subjects and Methods: The present study was conducted on 1349 participants which were divided into three groups on the basis of their symptoms. Group A – No symptoms (n = 439), Group B – Hypotonus pfd (n = 658), and Group C – Hypertonus pfd (n = 252). Examination: Vaginal examination to assess the pelvic floor muscles relaxation and contraction was done by Het’s Manual Muscle Testing (MMT). Inter rater reliability was assessed by comparing the data of two independent examiners on the same day. The intra rater reliability was assessed by comparing the data of test and retest at an interval of 1 week. Results: The intra rater reliability at 95% confidence interval (CI) was 0.92 – Normal pelvic floor function, 0.96 – Hypotonus pfd, and 0.97 – Hypertonus pfd. Moreover, inter rater reliability at 95% CI was 0.93 – normal pelvic floor function, 0.95 for hypotonus pfd, and 0.98 – hypertonus pfd. Conclusions: This study concludes Het’s MMT is a highly reliable manual muscle testing tool to assess the pelvic floor muscles.